Genome-wide AP2/ERF analysis identifies HmaERF87 as a positive regulator of Hydrangea macrophylla leaf spot resistance - Shuyuan Chen; Xintong Liu; Chengwei Zhang; Ziqin Zhang; Huijie Chen; Yong Han; Shuangshuang Chen; Jing Feng; Guangling Wang; Chang Li; Zedong Wu; Yanming Deng (Plant Cell Reports, 2026)

Fe/FeF2 Mott-Schottky heterojunction with the spontaneous charge transfer boosting the bifunctional oxygen electrocatalysis performance - Nanping Deng; Jinyu Han; Hao Chi; Yewen Shui; Xinyi Li; Chengwei Liu; Gang Wang; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2026)

Inverse Rayleigh wave dispersion curves via improving artificial fish swarm algorithm - Chengwei Zhang; Hongyan Shen; Han Che; Hao Wang; Shisheng Feng; Kanglogn Wang (Acta Geophysica, 2026)

Evaluating urban nighttime lighting and perceived safety in residential areas: An empirical investigation in Xi’an City - Chengwei Liu; Ling Liu; Xinxing Wang; Beilei Han; Leyi Chen (Building and Environment, 2026)

Modeling wave–structure interactions using fully nonlinear potential flow approach for deformable monopile foundations - Jiawang Liu; Shutong Xu; Hongfei Mao; Chengwei Han; Jianbo Han (Ocean Engineering, 2026)

Innovative design of CXCR4 cyclic peptide via molecular docking for 99mTc-Labeled SPECT/CT imaging in melanoma - Xianrui Yin; Xin Wang; Chengwei Chen; Shenglan Jia; Wanhong Li; Yihong Wu; Xin Chen; Danling Feng; Wai Ping Cecilia Tsang; Zhihao Han; Yueqing Gu (Analytica Chimica Acta, 2026)

Anatase-free titanosilicate with quasi-pure octahedral titanium species for efficient selective oxidations with hydrogen peroxide - Yan Gao; Yao Xiao; Chengwei Zhai; Jilong Wang; Fanrong Xu; Hailang Liu; Jing Liu; Han Jiang; Shaoqing Jin; Baocheng Lu; Xinrui Jiang; Huanhao Chen; et al. (Chemical Engineering Journal, 2025)

High-frequency resonance of bottom-fixed monopile-supported offshore wind turbines under nonlinear waves - Jiawang Liu; Shutong Xu; Hongfei Mao; Chengwei Han; Jianbo Han (Ocean Engineering, 2025)

Nanoplastics reshape lipid metabolism in marine microalgae with potential ecological consequence - Yajing Liu; Tianle Xi; Jia Liu; Han Jiang; Xiaowen Zhang; Naihao Ye; Chengwei Liang (Journal of Hazardous Materials, 2025)

Numerical simulation of GPR via Leapfrog ADI-FDTD - Bohua Wang; Hongyan Shen; Han Che; Shuai Liu; Chi Wang; Chengwei Zhang; Hao Wang; Shisheng Feng; Kanglong Wang (Journal of Applied Geophysics, 2025)

Application of microalgae in remediation of heavy metal-contaminated soils and its stimulatory effect on wheat growth - Jia Liu; Yajing Liu; Han Jiang; Xiaokun Yang; Xiaowen Zhang; Yukun Wu; Naihao Ye; Chengwei Liang (Algal Research, 2025)

Inversion of Rayleigh wave dispersion curves integrating the Osprey–Cauchy and Pigeon-inspired optimization algorithm - Shuai Liu; Hongyan Shen; Han Che; Bohua Wang; Chi Wang; Chengwei Zhang; Guangzhou Shao; Shisheng Feng; Hao Wang; Kanglong Wang (Acta Geophysica, 2025)

Evaluation of extraction-oxidation synergistic remediation of contaminated dredged sediment and plant suitability effects - Wenchao Yang; Jize Liu; Yuanshu Sun; Zhaowei Wang; Chengwei Han; Jianbo Han (Frontiers in Marine Science, 2025)
Generally, marine dredged sediments often exhibit co-pollution with heavy metals and petroleum hydrocarbons. This work investigates the extraction-oxidation synergistic remediation treatment of heavy metals (Cu and Pb) and total petroleum hydrocarbon (TPH) in the contaminated dredged sediments. The leachability of heavy metals, the oxidation of TPH, the physicochemical properties of the treated sediment, and the fertility of the treated sediment for barley growth are compared among different combinations of extractants [ethylene diamine tetraacetic acid (EDTA), citric acid (CA) and ferric chloride (FeCl 3 )] and oxidant [potassium persulfate (K 2 S 2 O 8 )]. The results show that the extraction-oxidation synergistic remediation treatment significantly reduces the Cu and Pb contents. The total removal performances of heavy metals and TPH in the contaminated dredged sediments by each co-remediation treatment group are FeCl 3 +Ox > EDTA-Ox > CA-Ox. Specifically, FeCl 3 +Ox and EDTA-Ox achieve the highest removal rates of 91.10% and 96.95% for Cu and Pb, respectively. The extractant affects the activation of K 2 S 2 O 8 by transition metals, enhancing the removal efficiency of TPH. The EDTA-Ox treatment group demonstrates the optimal treatment efficiency (37.42%) for TPH in the dredged sediment in 30 min. In the barley planting experiment, both shoot and root germinations in the EDTA-Ox treatment group reach their maximum values of 100% and 90%, respectively. Additionally, the CA-Ox treatment group exhibits maximal shoot and root lengths of 11.6 cm and 12.1 cm, respectively. The stress caused by salinity on seeds is also mitigated by the treatment. This study can provide technical support for the beneficial use of the dredged sediment.

Interpretable regional meteorological feature extraction enhances deep learning for extended 120-h PM2.5 forecasting - Xinyi Liu; Xueting Pu; Chengwei Lu; Han Zhang; Tao Li; Michael L. Grieneisen; Jucheng Li; Ning Ma; Chang Yan; Yu Zhan; Fumo Yang (Journal of Cleaner Production, 2024)

SIZ1-mediated SUMOylation of CPSF100 promotes plant thermomorphogenesis by controlling alternative polyadenylation - Zhibo Yu; Jun Wang; Cheng Zhang; Qiuna Zhan; Leqian Shi; Bing Song; Danlu Han; Jieming Jiang; Junwen Huang; Xiaolin Ou; Zhonghui Zhang; Jianbin Lai; et al. (Molecular Plant, 2024)

Preparation technology and preservation mechanism of novel Ag NPs-loaded ZIF-67 packaging film - Lixin Kang; Qiufang Liang; Yuxuan Liu; Arif Rashid; Abdul Qayum; Chengwei Zhou; Xu Han; Xiaofeng Ren; Zhuzhong Chi; Runhao Chi; Haile Ma (Food Packaging and Shelf Life, 2024)

Capacity assessment of the recurrent disposal of dredged materials in a marine disposal area - Congfang Ai; Yuxiang Ma; Chengwei Han; Guohai Dong; Jianbo Han (Ocean & Coastal Management, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

SlbHLH152, a bHLH transcription factor positively regulates iron homeostasis in tomato - Xiaoli Li; Haohao Cao; Deshui Yu; Kedong Xu; Yi Zhang; Xinxin Shangguan; Xiaohong Zheng; Zhongzhou Yang; Chaoqiong Li; Xingchen Pan; Yiming Cui; Zhiqing Zhang; et al. (Plant Science, 2023)

Meningeal lymphatics restoration and neurovascular protection synergistically improve traumatic brain injury treatment - Jingquan Lin; Hangxiang Sun; Hongjie Jiang; Rui Xue; Bing Qin; Jianan Lu; Zhoule Zhu; Chengwei Cai; Jiawei Han; Jianmin Zhang; Xiaohua Yu; Junming Zhu (Chemical Engineering Journal, 2023)

Improving calcium citrate food functions through spherulitic growth in reactive crystallization and a mechanism study - Hui Yan; Yanbo Liu; Haoyu Peng; Kangli Li; Chengwei Li; Shuixing Jiang; Mingyang Chen; Dandan Han; Junbo Gong (Food Chemistry, 2023)

Quantitative Fluorescence Resonance Energy Transfer Analysis on the Direct Interaction of Activation-2b with Histone H3/Switch-3B Protein in Arabidopsis Mesophyll Protoplasts - Lu Gao; Fangrui Lin; Danlu Han; Jieming Jiang; Chengwei Yang; Zhengfei Zhuang; Tongsheng Chen (Journal of Fluorescence, 2021)

Identification of genes under positive selection reveals evolutionary adaptation of Ulva mutabilis - Jian Zhang; Xiaowen Zhang; Wentao Han; Xiao Fan; Yitao Wang; Dong Xu; Yan Zhang; Jian Ma; Chengwei Liang; Naihao Ye (Acta Oceanologica Sinica, 2020)

Resistance spectrum assay and fine mapping of the blast resistance gene from a rice experimental line, IRBLta2-Re - Shen Chen; Jing Su; Jingluan Han; Wenjuan Wang; Congying Wang; Jianyuan Yang; Liexian Zeng; Xiaojing Wang; Xiaoyuan Zhu; Chengwei Yang (Euphytica, 2014)

Silencing of TaBTF3 gene impairs tolerance to freezing and drought stresses in wheat - Guozhang Kang; Hongzhen Ma; Guoqin Liu; Qiaoxia Han; Chengwei Li; Tiancai Guo (Molecular Genetics and Genomics, 2013)